Analysis of maternal factors and food security with the incidence of stunting in children 0-59 months of age in Sungai Penuh City - Illiyin Tri Nashira; Kusnandar Kusnandar; Ika Sumiyarsi Sukamto (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The high incidence of stunting is the leading cause of death in children under five years of age worldwide. Sungai Penuh City is one of the urban areas in Indonesia that has experienced an increase in the prevalence of stunting. Stunting is caused by long-term nutritional deficiency in the mother due to inadequate food supply due to low household food security. Stunting can also occur because of the reproductive condition of the mother, who is not ready to conceive. This cross-sectional study aimed to analyze maternal factors and food security that have the greatest influence on the incidence of stunting in toddlers aged 0-59 months in Sungai Penuh City using data from the 2022 Indonesian Nutrition Status Survey conducted in August-September 2022. The sample consisted of 308 toddlers living in urban areas. Data were analyzed using descriptive non-parametric statistical tests with the chi-square test and Logistic Regression test. The results of this study prove that short maternal stature has a significant relationship with the incidence of stunting in toddlers (p<0,05), whereas chronic energy deficiency mothers, maternal age, and food security did not have a significant relationship with the incidence of stunting in toddlers in urban areas (p>0,05). Maternal short stature is an indicator of past chronic malnutrition and a major predictor of stunting in children under five